The relationship between the Length of Injections Contraception Progestin (Depoprovera) with blood pressure in the acceptor of family planning in health center II South Denpasar 2012 - DAEP Ardarsini (Program Studi Sarjana Ilmu Keperawatan dan Profesi Ners, Fakultas Kedokteran, Universitas Udayana, 2013)
Contraceptive services as part of the family planning program is needed to make efforts to improve the quality of life for residents. Contraception most widely used type of progestin injections of the contraceptive injection (depoprovera). One disadvantage of the use of contraception is a change in serum lipids on long-term use, which obtained a decrease in levels of High Density Lipoprotein-cholesterol (HDL-cholesterol) that may increase the risk of increased blood pressure. This study aims to determine the relationship between duration of use of contraceptive progestin injections (depoprovera) with blood pressure in family planning acceptors. This study is a descriptive study of correlation with cross-sectional approach is performed on the 60 respondents were selected by purposive sampling. Methods of data collection is done with interviews and observations by means of a sheet of interviews as well as blood pressure gauges. The result of from this research at most responder use the contraceptive injection for 12-24 months, with as many as 28 people or 46.7% classified as pre-hypertension, the remaining 32 people or 53.3% had normal blood pressure. Based on the analysis results using Spearmen Rank correlation test (p <0.05), obtained the value p = 0.018, meaning there is a significant relationship between duration of use of contraceptive progestin injections (depoprovera) with blood pressure in family planning acceptors in health center II South Denpasar. From these results expected in the use of contraceptive progestin injections (depoprovera) are all concerned about the long-time usage and side effects, especially on blood pressure.